Penggunaan Aplikasi Android untuk Meningkatkan Keterampilan Guru dalam Bidang Teknik Instalasi Motor Listrik: Pengabdian - Ahmad Dani; Dino Erivainto (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The training Using Android Apps to Improve Teachers’ Skills in Electric Motor Installation Engineering at SMK-TR Sinar Husni Labuhan Deli was conducted to address this issue. The training aims to improve teachers' understanding of Android applications, the benefits of information technology, and its application in designing electric motor installation circuits. The training method includes theoretical and practical sessions. The theoretical sessions included an introduction to Android applications, basic principles of information technology, and renewable energy. Practical sessions involved hands-on simulations of the use of Android apps, interactive discussions, and case studies. The training results showed a significant increase in teachers' knowledge and skills in using Android apps. Teachers were also more creative in developing learning materials and motivated to innovate. The positive impact is felt on students, with more interactive learning methods, increasing their interest in learning and preparing them for the world of work. The training also strengthened the collaboration between Universitas Pembangunan Panca Budi and SMK-TR Sinar Husni, improving teacher competence and the relevance of graduates to industry needs. Overall, the training provided great benefits for teachers, students, and educational institutions, and contributed significantly to advancing the quality of vocational education in Indonesia.